Ovarian Cyst Cured with Natrum Muriaticum 30: A Case Report (Advancements in Homeopathic Research, 2022)
A case of large complex unilateral right ovarian cyst resolved with holistic approach with Natrum Muriaticum 30 in 4 months treatment. A girl aged 17 years approached for treatmentof large complex right ovarian cyst on 13 Sep 2019. She had previously consulted agynaecologist for moderate dysmenorrhea which has persisted since 2017 and was advised ultrasonography of pelvis which revealed the aforementioned pathology for which she was recommended surgery.Drug h/o: Dolo off and on for dysmenorrhea Family h/o: Mother-hypothyroidism Initial ultrasonography of pelvis region (14 Aug 2019): Figure 1 & 2
Keywords: ovarian cyst; gynaecologist; dysmenorrhea; ultrasonography; surgery.